Executing mortgage auctions in insolvency: A study on normative conflicts, legal certainty, and separate creditor protection - Lydia Fransiscani Br. Turnip (Institute Of computer Science (IOCS), 2024)
This paper discusses the normative asynchronousness between the Mortgage Rights Law (UUHT) and the Bankruptcy Law in the execution of mortgage collateral object auctions during insolvency. Secured creditors, such as banks, face restrictions in executing mortgage rights even though Article 6 of the UUHT normatively grants direct execution rights. This research utilizes a normative legal approach with techniques including analysis of legal regulations, a comparison of the Dutch and German legal systems, and literature review. The findings indicate that there is legal uncertainty in the practical execution of collateral object auctions during insolvency, and that the protection of secured creditors is limited and dependent on the interpretations of curators and courts. The author argues that the position of secured creditors, such as banks, should be given stronger legal certainty guarantees within the framework of property rights protection and legal certainty.